2021
DOI: 10.1002/pc.26343
|View full text |Cite
|
Sign up to set email alerts
|

Compressive fatigue behavior of external patch repaired carbon/epoxy composites

Abstract: This work involves an experimental investigation of the external patch repaired woven carbon fiber-reinforced polymer laminates under load controlled constant amplitude compressive fatigue loading. The specimens of parent laminates with stacking sequence [0/45] s and [45/0] s were both repaired with two types of precured patches viz. [0] 2 and [45] 2 representing high stiff and low-stiff cases. Digital image correlation and acoustic emission were employed to obtain the insight to the development of distinctive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Drilling several small circular holes at the BVID area could result in a cascading effect on the repair performance, as the drilling action could aggravate the BVID. [34][35][36] Our past studies revealed that drilling holes could result in diminution of laminate properties value (namely fracture strength, fracture strain, resilience, and fracture toughness) but no trend was observed with increasing VH numbers. [21,37] Furthermore, there was no effect of hole-hole orientation (row of holes parallel/perpendicular to the applied load direction) and hole-hole separation distance (where the VHs were confined within the BVID region) on the mechanical properties.…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…Drilling several small circular holes at the BVID area could result in a cascading effect on the repair performance, as the drilling action could aggravate the BVID. [34][35][36] Our past studies revealed that drilling holes could result in diminution of laminate properties value (namely fracture strength, fracture strain, resilience, and fracture toughness) but no trend was observed with increasing VH numbers. [21,37] Furthermore, there was no effect of hole-hole orientation (row of holes parallel/perpendicular to the applied load direction) and hole-hole separation distance (where the VHs were confined within the BVID region) on the mechanical properties.…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…The authors reported the low stiff patch [45] 2 and repairing the load‐bearing plies of parent laminate ([0/45] s ) showed the highest load recovery. Bhatia and Arockiarajan 27,28 also analyzed the effect of patch stiffness and parent laminate stacking sequence in compressive and flexural static and fatigue loading cases. The authors reported that the effect of stiffness is not pronounced in these loading cases.…”
Section: Introductionmentioning
confidence: 99%
“…This repair technique for laminated plates could serve as a reference for repairing honeycomb sandwich structures. Bhatia and Arockiarajan 10 conducted compressive fatigue tests on the repaired woven CFRP laminates, and the results showed that the external patch repair restored the compressive fatigue performance of the specimens. Mahdi et al 11 conducted four‐point bending tests on undamaged and repaired sandwich beams.…”
Section: Introductionmentioning
confidence: 99%